2014
DOI: 10.2298/hemind121102027j
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of ethanolic extract of Penicillium chrysogenum and Penicillium fumiculosum

Abstract: The aim of this study was to investigate the biological and chemical activity on two species of fungi of the genus Penicillium isolated from wastewater. On the selected species of fungi the different antioxidant activity assays were carried out: DPPH free-radical scavenging activity, total antioxidant activity, Fe2+- chelating ability and Fe3+- reducing power. Total phenol content was also determinate for ethanolic extract of mycelia. Penicillium chrysogenum ethanolic extract contained higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
21
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 30 publications
5
21
4
Order By: Relevance
“…The slight difference between the antioxidant capacities of EAF and ascorbic acid may be explained either by the purity of ascorbic acid, whereas the extract of A. creber is a mixture of multiple compounds or by the capacity of some compounds in the fungal extract to neutralize or to inhibit the effect of active compounds (Dhankhar et al 2012). Moreover, our data revealed that A. creber is able to produce much higher content of phenols than the other filamentous fungi in the literature (Jakovljević et al 2014;Smith et al 2015;Sugiharto et al 2016). Many previous studies attributed the antioxidant activity of filamentous fungi to their TPC (Abdel-Monem et al 2013;Smith et al 2015, Nwobodo et al 2017.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…The slight difference between the antioxidant capacities of EAF and ascorbic acid may be explained either by the purity of ascorbic acid, whereas the extract of A. creber is a mixture of multiple compounds or by the capacity of some compounds in the fungal extract to neutralize or to inhibit the effect of active compounds (Dhankhar et al 2012). Moreover, our data revealed that A. creber is able to produce much higher content of phenols than the other filamentous fungi in the literature (Jakovljević et al 2014;Smith et al 2015;Sugiharto et al 2016). Many previous studies attributed the antioxidant activity of filamentous fungi to their TPC (Abdel-Monem et al 2013;Smith et al 2015, Nwobodo et al 2017.…”
supporting
confidence: 55%
“…Antioxidant analysis 2,2-diphenyl-1-picryl hydrazyl (DPPH) assay. The DPPH radical scavenging activity was determined according to Jakovljević et al (2014). Different concentrations of EAF were prepared: 12.5, 25, 50, 100, 200, 400 µg/ml.…”
mentioning
confidence: 99%
“…However, natural resources of mycochemicals are safe and better substitutes for chemical antioxidants [5]. Fungi are an important source of natural antioxidants because of their natural ability to produce secondary metabolites [6]. ey contain antioxidants in the form of steroids, quinones, alkaloids, phenylpropanoids, tocopherol, phenols, tannins, lactones, terpenoids, triterpenes carotenoids, and flavonoids [7].…”
Section: Introductionmentioning
confidence: 99%
“…Essential mycochemicals contained in fungi such as phenolic contents have attained more interest due to their characteristics to inhibit disease by their antioxidant activity. Phenols and flavonoids are the major secondary metabolites of fungi [6]. Moreover, phenolic and flavonoids contents of fungal origin act as potential therapeutic agents, i.e., antimutagenic, antibiotics, anticarcinogenic, and antioxidants [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation